Anterosuperior protraction of maxillae using the extraoral device, RAMPA; finite element method. Issue 13 (3rd October 2018) - Mitani, Yasushi; Choi, Bumkyoo; Choi, Jaehyuk
Abstract: This paper presents a boosting effect against gravity by analyzing the displacement and stress distribution of craniofacial structures due to the protraction of the extraoral device, the Right Angle Maxillary Protraction Appliance(RAMPA) system, including semi-rapid maxillary expansion (sRME) using the finite element method. In addition, a patient case was illustrated and compared with the results calculated from a simulation. The results from the finite element method were obtained for 0.5 mm activation using the screw of the intraoral device, gHu-1. This study reveals that RAMPA rotates the patient's maxilla and mandible in the forward direction and forces them to move forward and upward.